New nitrogen uptake strategy: specialized snow roots - Vladimir G. Onipchenko; Mikhail I. Makarov; Richard S. P. Van Logtestijn; Viktor B. Ivanov; Assem A. Akhmetzhanova; Dzhamal K. Tekeev; Anton A. Ermak; Fatima S. Salpagarova; Anna D. Kozhevnikova; Johannes H. C. Cornelissen (Ecology Letters, 2009)
The evolution of plants has yielded a wealth of adaptations for the acquisition of key mineral nutrients. These include the structure, physiology and positioning of root systems. We report the discovery of specialized snow roots as a plant strategy to cope with the very short season for nutrient uptake and growth in alpine snow‐beds, i.e. patches in the landscape that remain snow‐covered well into the summer. We provide anatomical, chemical and experimental 15 N isotope tracking evidence that the Caucasian snow‐bed plant Corydalis conorhiza forms extensive networks of specialized above‐ground roots, which grow against gravity to acquire nitrogen directly from within snow packs. Snow roots capture nitrogen that would otherwise partly run off down‐slope over a frozen surface, thereby helping to nourish these alpine ecosystems. Climate warming is changing and will change mountain snow regimes, while large‐scale anthropogenic N deposition has increased snow N contents. These global changes are likely to impact on the distribution, abundance and functional significance of snow roots.